The status of airspace for unmanned aerial vehicles (UAVS) and the issue of airspace trespass: the Tawhidic epistemology approach - Onn, Norhusna Emirah (Global Academic Excellence, 2026)
This paper evaluates the legal status of airspace and the concept of ownership in relation to the unmanned aerial vehicles (UAVs) and the issue of trespass through the lens of Tawhidic epistemology. The current Malaysian legal framework and international level reveal a significant loophole, as the UAV operational airspace has yet to be formally declared, creating uncertainty over ownership, control, and liability. Tawhidic views the integration of ownership as trust (amanah) and serves for the public interest (maslahah). Drawing from the Islamic jurisprudence on the doctrine of ownership, this research argues that airspace governance must reflect both divine unity and human accountability. The dynamic principle of revival of dead land (ihya al-mawat) enriches this analysis by emphasising the concept of UAV airspace as mawat land that can be cultivated within the concept of ownership of airspace. Within this framework, customary practice ('urf) plays a vital role in shaping the contextual application of the rule, which is consistent with the higher objective of shariah (maqasid al-shariah). The hybrid approach of this research consequently solves the issue of airspace ownership for UAVs by combining doctrinal legal analysis with epistemological reasoning